INDEPENDENCE OF THE CURATOR IN THE MANAGEMENT AND DISPOSAL OF BANKRUPTCY PROPERTY - Zul Pahmi Harahap; Fitri Rafianti; Henry Aspan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The curator has an important role in a bankruptcy to manage and settle the bankruptcy assets. Article 1 point 5 of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations states that what is meant by Curator is the Inheritance Property Office or an individual appointed by the court to manage and settle the assets of a bankrupt debtor under the supervision of a supervising judge. In carrying out the task of settling and managing bankruptcy assets, the curator must be independent and not take sides with either party. What is the curator's responsibility for the risk of loss in the Management and Settlement of Bankruptcy Assets? What is the curator's authority over bankrupt debtors who are not cooperative in a bankruptcy process? This research is normative legal research, the research was carried out by reviewing secondary data in the form of library materials, which include primary materials, secondary and tertiary materials. The entire data obtained (secondary data and primary data) was then processed systematically and qualitatively to produce writing. analytical descriptive. In this case, the researcher conducted an analytical juridical study to see the role and responsibilities of the curator in the management and settlement of bankruptcy assets.